Dynamic absorber for ropeway gondola using Coriolis force - Matsuhisa, Hiroshi; Yasuda, Masashi (Vietnam Journal of Mechanics, 2008)
Wind-induced swinging of ropeway gondola can be reduced using dynamic absorbers. To maximize the performance of conventional dynamic absorbers, their location should be as high as possible. However, absorbers can not be installed at high positions due to interference issues with structures such as towers and stations. To address this problem, a new type of dynamic absorber that moves vertically is proposed. This absorber is composed of a mass supported by a spring. The mass moves in the radius direction (up and down) and it induces Coriolis force in the circumference direction to prevent the swing of gondola. If the natural frequency of the absorber is tuned to twice that of the gondola, the absorber moves spontaneously with a large amplitude due the resonance. This absorber is more effective when it is located at lower positions. The experiment with a small model and an actual gondola for 10 passengers were carried out and the results agreed well with the theoretical predictions